2017
DOI: 10.1002/biof.1366
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of oleuropein

Abstract: Cancer cells exhibit enhanced proliferation rate and a resistance to apoptosis. Epidemiological studies suggest that olive oil intake is associated with a reduced risk of cancer. Olive oil, olives, and olive leaves contain many polyphenols, including oleuropein. Recently, several studies have demonstrated that oleuropein inhibits proliferation and induces apoptosis in different cancer cell lines. In addition, anticancer effects of oleuropein have been seen in animal studies. These effects are associated with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 81 publications
1
81
0
1
Order By: Relevance
“…Given our previous evidence for the protective role of Ole in neurodegenerative and cardiovascular diseases [40][41][42][43], we have decided to investigate whether Ole might exert some role in melanoma treatment. The existing studies indicate that Ole express a well-demonstrated protective role against many types of cancer [22]. Most of the studies have investigated the anticancer effects of Ole on breast cancer, disclosing that the polyphenol may not only decrease cell viability and proliferation [44] and synergize with Doxorubicin in in vitro and in vivo model [25,45], but also may reverse resistance toward the chemotherapeutic agent, Trastuzumab [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given our previous evidence for the protective role of Ole in neurodegenerative and cardiovascular diseases [40][41][42][43], we have decided to investigate whether Ole might exert some role in melanoma treatment. The existing studies indicate that Ole express a well-demonstrated protective role against many types of cancer [22]. Most of the studies have investigated the anticancer effects of Ole on breast cancer, disclosing that the polyphenol may not only decrease cell viability and proliferation [44] and synergize with Doxorubicin in in vitro and in vivo model [25,45], but also may reverse resistance toward the chemotherapeutic agent, Trastuzumab [46].…”
Section: Discussionmentioning
confidence: 99%
“…Ole has been reported to have many pharmacological properties, among which antioxidant, anti-inflammatory, cardioprotective, neuroprotective and hepatoprotective [20,21]. Recently accumulating in vitro and in vivo experiments together with epidemiological and clinical data, have provided support to the anti-tumor properties of Ole toward different tumor histotypes, such as breast, colon and lung cancer [22,23]. What is of translational importance, Ole was found to be a powerful sensitizer of Doxorubicin-mediated killing of prostate and breast cancer cells [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, anticancer effects of oleuropein have been seen in animal studies. These effects are associated with oleuropein's ability to modulate gene expression and activity of a variety of different signalling proteins that play a role in proliferation and apoptosis .…”
Section: Hesham Shamshoum Filip Vlavcheski Evangelia Tsianimentioning
confidence: 99%
“…The most widely investigated olive phenolic compounds include, oleuropein, hydroxytyrosol, tyrosol and oleocanthal (Figure 1). The potential beneficial health effects and cellular and molecular mechanisms of oleuropein, hydroxytyrosol and tyrosol have been reviewed extensively (22–29). Oleocanthal also represents an important phenolic compound in extra-VOO, which has been shown to possess potent antioxidant and anti-inflammatory effects, at least in part, through non-specific inhibition of cyclooxygenase-1 and -2 enzymes (30, 31).…”
Section: Introductionmentioning
confidence: 99%